The Effect of Village Fund Cash Transfer on Food Consumption - Muhammad Anisulfuad; Evi Yulia Purwanti (Efficient: Indonesian Journal of Development Economics, 2023)
The Covid-19 pandemic has caused economic problems in Patebon District. Village fund cash transfer is a program to help increase food consumption for poor households and those affected by the Covid-19 pandemic. This study aims to analyze the effect of village fund cash transfer on the level of food consumption of Beneficiary Families (KPM) after receiving village fund cash transfer. This research was conducted by interviewing 89 KPM village fund cash transfer in Patebon District. The analysis was conducted using one dependent variable, namely the level of household food consumption and five independent variables, namely the village fund cash transfer, household income, number of family dependants, head of household job status, and head of household education. The analysis was performed using logistic regression. Household income and the number of family dependants have a significant effect on the level of change in household food consumption. Meanwhile, the village fund cash transfer, head of household job status, and head of household education have no significant effect on the level of change in household food consumption.